An investigation of the role of learning conversations in youth's authoring of science identities during an informal science camp. Issue 1 (2nd January 2017) - Riedinger, Kelly; McGinnis, J. Randy
ABSTRACT: In this investigation, we examined how youth during learning conversations at an informal science education camp negotiated and authored identities as learners of science. Using identity theory as our analytical lens, we investigated by application of qualitative methodology the socially constructed nature of youth's identities. We focused on the ways in which learning conversations at the science camp prompted changes in learners' identity as they engaged in science. Data collection included videotaped observations, field notes, interviews, and journal entries. Interaction analysis and constant comparison were used to develop analytic lenses. The results of our study highlighted the unique affordances of informal science education settings for supporting youth's identity work in science. In particular, we describe how youth negotiated and authored identities as learners of science through positioning, discourse, and performance. Our study contributed essential insights drawn from empirical data on how youth in an informal science education experience—a science camp—socially negotiated their identities during learning conversations.